(untitled) («CONTEMPORARY TECHNOLOGIES OF COMPUTATIONAL LINGUISTICS», 2024)
This article examined the discursive approach to the study of political texts - an important rule of modern political linguistics, as well as the relationship of each specific text with other texts within the current political situation.